2018
DOI: 10.1111/jvim.15052
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin D Receptor Expression in Dogs

Abstract: BackgroundThere is growing evidence linking low blood vitamin D concentration to numerous diseases in people and in dogs. Vitamin D influences cellular function by signaling through the vitamin D receptor (VDR). Little is known about which non‐skeletal tissues express the VDR or how inflammation influences its expression in the dog.ObjectivesTo define which non‐skeletal canine tissues express the VDR and to investigate expression in inflamed small intestine.AnimalsThirteen non‐skeletal tissues were collected p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(19 citation statements)
references
References 72 publications
0
19
0
Order By: Relevance
“…One study measured lower vitamin D levels in cats with IBD and intestinal lymphoma (36). Chronic kidney disease can eventually result in lower plasma 1,25(OH)2D3 due to reductions in synthesis (34, 37). Thus, vitamin D status can be altered in cats and dogs secondary to inflammation, decreased absorption or synthesis and increased loss.…”
Section: Discussionmentioning
confidence: 99%
“…One study measured lower vitamin D levels in cats with IBD and intestinal lymphoma (36). Chronic kidney disease can eventually result in lower plasma 1,25(OH)2D3 due to reductions in synthesis (34, 37). Thus, vitamin D status can be altered in cats and dogs secondary to inflammation, decreased absorption or synthesis and increased loss.…”
Section: Discussionmentioning
confidence: 99%
“…Quantitative PCR analysis of target gene was executed using Biorad CFX96 Real time-PCR taking human housekeeping gene, GAPDH as a reference. Previously reported primers for qPCR analysis of target and reference gene were selected for this study 78 , 79 following the standard protocol 80 . Relative gene expression analysis from qPCR data was performed using the Relative Expression Software Tool (REST® 2009) 81 that utilises the expression of reference genes to normalize expression of target genes in different samples.…”
Section: Methodsmentioning
confidence: 99%
“…Although VDR is widely expressed in all tissues in dogs, the colon of healthy dogs is the only place where its expression is weak, unlike humans and other species (Cartwright et al, 2018). In humans and mice used as an experimental model for ulcerative colitis, the VDR expression was negatively related to colonic inflammation; however, in studies carried out by Cartwright et al (2018) no changes in VDR expression were observed in dogs with inflammatory bowel disease. The authors also observed that the expression of VDR was not correlated with the presence of inflammation, which, may confer an advantage for the treatment of these animals with vitamin D replacement.…”
Section: Vitamin D and Gastrointestinal Diseasesmentioning
confidence: 99%
“…Finally, this may still have a positive effect on the expression of FOXP3 and the formation of induced regulatory T cells (Mora et al, 2008). Although VDR is widely expressed in all tissues in dogs, the colon of healthy dogs is the only place where its expression is weak, unlike humans and other species (Cartwright et al, 2018). In humans and mice used as an experimental model for ulcerative colitis, the VDR expression was negatively related to colonic inflammation; however, in studies carried out by Cartwright et al (2018) no changes in VDR expression were observed in dogs with inflammatory bowel disease.…”
Section: Vitamin D and Gastrointestinal Diseasesmentioning
confidence: 99%